Diseño de talleres educativos para el fortaleciminto de valores humanos en los estudiantes de octavo año de educación básica del Colegio “Nacional Poaló” de la parroquia Poalo en el año lectivo 2012-2013 - Chanaluisa Chanaluisa, Susana Veronica (2015)
The aim of this thesis was: "Designing educational workshops to strengthen values in students of eighth year of Basic General Education National College Poalo school year in 2012 - 2013". This study began with the problem How to design educational workshops help develop human values? The research was based on qualitative and quantitative, study by collecting and processing the information gathered to understand, analyze and interpret the educational phenomenon and explain truthfully. The purpose of this research work was established in building activities. The conclusions of this work are: the practice of values are not consolidated in the educational community, there are values that are not practiced, little class participation, fights among peers and have not developed educational workshops. The contribution of this work is to develop 10 educational workshops to help strengthen human values in the educational community of the research institution.